Genetic diversity of Plasmodium vivax reticulocyte binding protein 2b in global parasite populations - Zhang X. (2023)
Background: Plasmodium vivax reticulocyte binding protein 2b (PvRBP2b) plays a critical role in parasite invasion of reticulocytes by binding the transferrin receptor 1. PvRBP2b is a vaccine candidate based on the negative correlation between antibody titers against PvRBP2b recombinant proteins and parasitemia and risk of vivax malaria. The aim of this study was to analyze the genetic diversity of the PvRBP2b gene in the global P. vivax populations. Methods: Near full-length PvRBP2b nucleotide sequences (190–8349 bp) were obtained from 88 P. vivax isolates collected from the China–Myanmar border (n = 44) and Thailand (n = 44). An additional 224 PvRBP2b sequences were retrieved from genome sequences from parasite populations worldwide. The genetic diversity, neutral selection, haplotype distribution and genetic differentiation of PvRBP2b were examined. Results: The genetic diversity of PvRBP2b was distributed unevenly, with peak diversity found in the reticulocyte binding region in the N-terminus. Neutrality analysis suggested that this region is subjected to balancing selection or population bottlenecks. Several amino acid variants were found in all or nearly all P. vivax endemic regions. However, the critical residues responsible for reticulocyte binding were highly conserved. There was substantial population differentiation according to the geographical separation. The distribution of haplotypes in the reticulocyte binding region varied among regions; even the two major haplotypes Hap_6 and Hap_8 were found in only five populations. Conclusions: Our data show considerable genetic variations of PvRBPb in global parasite populations. The geographic divergence may pose a challenge to PvRBP2b-based vaccine development. Graphical Abstract: [Figure not available: see fulltext.].